2018
DOI: 10.1186/s12891-018-2359-1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative multiple low-dose Dexamethasones improves postoperative clinical outcomes after Total knee arthroplasty

Abstract: BackgroundThe purpose of this study was to investigate the efficacy and safety of multiple low-dose dexamethasones in primary total knee arthroplasty (TKA).MethodsOne hundred fifty patients were equally randomized into 3 groups: Group A (n = 50) received 2 doses of normal saline only; Group B (n = 50) received with 1 dose of intravenous dexamethasone and 1 dose of normal saline; Group C (n = 50) received with 2 doses of intravenous dexamethasone. The clinical outcomes and complications were assessed.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…Among these, 109 duplicates were excluded using Endnote X8 (Clarivate, Philadelphia, PA, USA), and 250 studies were removed on the basis of the title and abstract. Ten files 14 – 18 , 23 27 that met the inclusion criteria were ultimately identified after carefully and completely reading each of the 19 remaining studies. The specific process of including studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 109 duplicates were excluded using Endnote X8 (Clarivate, Philadelphia, PA, USA), and 250 studies were removed on the basis of the title and abstract. Ten files 14 – 18 , 23 27 that met the inclusion criteria were ultimately identified after carefully and completely reading each of the 19 remaining studies. The specific process of including studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A pain VAS following TKA was reported in nine studies. 14 – 18 , 23 26 All of these nine studies assessed VAS at 24 hours, 14 – 18 , 23 26 and the VAS at 48 hours was evaluated in six studies. 15 17 , 23 25 The pooled results demonstrated that perioperative intravenous low-dose dexamethasone decreased the postoperative pain score at 24 hours (SMD = −0.430; 95%CI: −0.570 to −0.291; P < 0.001) and 48 hours (SMD = −0.250; 95%CI: −0.405 to −0.096; P = 0.002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 , 24 , 25 Additionally, recent investigations into various non-narcotic perioperative medications have shown the potential to further reduce a patient’s overall need for pain medicine in the immediate postoperative period and improve outcomes. 19 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%